Why generation Z stays: The power of resilience and organizational commitment in reducing turnover intention - Diah Sofiah; Erlin Nur Puspasari (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to examine the mediating role of organizational commitment in the relationship between resilience and turnover intention among Generation Z employees in Indonesia. Previous research have shows resilience directly reduces turnover intention, while others find this effect is mediated by work engagement. This inconsistency highlights the need to explore mediating mechanisms, such as organizational commitment, in the resilience-turnover intention relationship. The study involved 193 Gen Z employees from a multinational corporation, with data collected through established and reliable measures of resilience(α = .962), organizational commitment ( α=.921) and turnover intention (α= .871). Mediation analysis conducted using JASP software revealed that resilience significantly decreased turnover intention through the pathway of continuance commitment (Z = –3.709, p < .001). In contrast, affective and normative commitments did not demonstrate significant mediating effects. Drawing Upon Conservation of Resources (COR) Theory, these findings suggest that Generation Z employees’ retention is primarily driven by concerns over potential losses of valuable resources, such as financial stability and career development opportunities, rather than affective or normative attachments to the organization. This study underscores the critical role of organizational commitment as a mechanism for retaining Gen Z employees and highlight that retention strategies should prioritize on enhancing resource-based incentives and reducing perceived resource loss rather than solely fostering emotional or normative engagement